Bütçesel katılımın iş tatmini üzerindeki etkisi - Akpınar, Görkem (Gebze Yüksek Teknoloji Enstitüsü, Lisansüstü Eğitim Enstitüsü, 2007)
Çalısmanın konusu, bütçesel katılım, bütçe hedeflerine baglılık ve is ile ilgili bilginin is tatmini üzerindeki etkilerinin arastırılmasıdır. Veri toplamada anket yöntemi kullanılmıstır. Anket Marmara bölgesinde faaliyet gösteren 127 orta ve büyük ölçekli isletmeye uygulanmıstır. Bu anketlerden uygun olmayan 23'ü elendikten sonra toplam 104 anketten elde edilen veri çalısmamızın örneklemini olusturmustur. Elde edilen veriyle, yöneticilerin bütçeleme sürecine katılımlarının artmasının onların bütçe hedeflerine baglılıklarını arttırdıgı sonucuna ulasılmıstır. Sirkette çalısan yöneticilerin bütçe hedeflerine baglılık ve isle ilgili bilgileri arttıkça yaptıgı isten tatmin olma düzeyleri ve motivasyonları artmaktadır. Fakat, diger degiskenlerle birlikte ele alındıgında, yöneticilerin bütçeleme sürecine katılımlarının, onların is tatminleri üzerindeki etkisinin direkt degil, dolaylı oldugu görülmüstür. Aynı zamanda, bütçesel katılımın isle ilgili bilgiyi olumlu yönde etkiledigi görülmüstür.

The subject of this study is investigating the effects of budgetary participation, budget goal commitment and job relevant information on job satisfaction. Method of data collection is questionnaire. The questionnaire has been filled out at 127 big/medium size enterprises, operating in Marmara region. Twenty three improper questionnaires have been eliminated, and the data collected from 104 questionnaires has become the sample of the study. According to the findings obtained by analyzing the collected data through regression; an increase in managers' participation to budgetary process increases their budget goal commitment. As long as managers' budget goal commitment and job relevant information increase, the level of their satisfaction with their job also increases and they become more motivated. But it has been found out that, when considered together with other variables, managers' participation to budgeting process does not have a direct, but rather an indirect effect on their job satisfaction. At the same time, it has been found out that budgetary participation has a positive effect on job relevant information.
Budgetary participation's effect on job satisfaction
Keywords: İşletme; Business Administration